Hyaluronic acid-solid lipid nano transporter serum preparation for enhancing topical tretinoin delivery: skin safety study and visual assessment of skin - Mehmood, Yasir; Shahid, Hira; Rizvi, Syeda Momena; Jamshaid, Usama; Arshad, Numera; Nur-e-Alam, Mohammad; Hussain, Muhammad Delwar; Kazi, Mohsin (Frontiers in Pharmacology, 2024)
The use of nanosized particles is becoming more popular for the topical treatment of skin conditions. In this research work, we created and investigated the effects of solid lipid nanoparticles (SLN) containing hyaluronic acid and tretinoin. Solvent emulsification diffusion method was used to prepare the SLN formulation and characterized for their physicochemical properties. Fourier transform infrared spectroscopy was used to confirm that hyaluronic acid and tretinoin were incorporated in the SLN. Furthermore, X-ray diffractogram, thermal analysis including DSC and TGA and in vitro dissolution, permeation tests were also performed along with microbial assessment. Clinical studies in human were performed to evaluate the effect of the SLN on skin wrinkles. The SLN was 750 ±31.29 nm in size, with a zeta potential of 13.07 ± 0.75 mV and a narrow polydispersity index of 0.24 ± 0.12. The entrapment efficiency of tretinoin was found to be 90.07 ± 4.79%. Clinical studies in healthy human volunteers demonstrated that 90% of the tested individuals had improved skin conditions (reduction in wrinkles), by at least one grade after 4 weeks of treatment.Regarding the development on SLN, it was found that the internal phase concentration did not considerably affect the physicochemical and microbiological properties. Therefore, Hyaluronic acid has potential for the development of SLN applicable to cosmetic formulations, especially for skin.These findings show that the developed SLN have potential for use as cosmetics in the future.